Perancangan Sistem Pengisian Capacitor Bank Secara Otomatis Pada Penendang Solenoid Robot Sepak Bola Universitas Jambi - Rustam Rustam; Yosi Riduas Hais (Universitas Batanghari Jambi, 2021)
One of the KRI fields is the Indonesian Football Robot Contest (KRSBI). In a match the robot does not know when the ball from the robot in one team is ready to be kicked into the opponent's goal. The kicking robot has an important role in creating goals against the opponent's goal. At the KRSBI solenoid kicker, Jambi University, using a booster converter zvz 390 to charge a capacitor bank which has a capacitance of 3900 F with a high voltage of 387 V, takes 6.34 seconds. However, 387 V is the maximum booster converter voltage. To minimize the occurrence of damage, a voltage of 310 V is set as the setpoint voltage for charging the capacitor bank with a charging time span of 4.3 seconds. Then the automatic control system for charging capacitor banks has a maximum error of 1.9%